Chondroid Syringoma of Dorsum of the Nose - Netra Aniruddha Pathak; Vidya Vasant Rokade; Kiran Jayawant Shinde (Bengal Journal of Otolaryngology and Head Neck Surgery, 2020)
IntroductionChondroid syrigomas are rare, usually benign tumors occurring predominantly in the head and neck area. These are also known as mixed tumors of skin. Preoperative diagnosis is difficult and generally histopathology examination confirms the diagnosis.  The usual presentation is that of a slowly growing mass.Case ReportA rare case of chondroid syringoma on dorsum of external nose in 30 year old female patient   is presented.DiscussionChondroid syringoma presents as slow‐growing, painless, subcutaneous or intracutaneous nodule in middle‐aged adult males. The tumor is often initially confused with more common dermatologic skin disorders such as sebaceous cysts, dermoid cysts, neurofibromas, dermatofibromas, basal cell carcinoma, histiocytoma and seborrheic keratosis. The treatment of choice is surgical excision with negative margins with follow-up to detect recurrences.